The Evaluation of The Community Development Program Through One Village One Product (OVOP) By The Villaguaraenim District - Yurismasari, Heidi; Hendarso, Yoyok; Nadjib, Abdul (Green Publisher Indonesia, 2025)
The One Village One Product (OVOP) program is one of the strategic initiatives to improve community welfare through the development of village superior products based on local potential. This study aims to evaluate the implementation of the OVOP program by Kumu Village, Muara Enim Regency, using a descriptive qualitative approach. Data were collected through interviews, observations, and analysis of program documents. The results showed that the OVOP program has had a positive impact in improving community skills, creating jobs, and increasing the added value of local products. However, there are several obstacles, such as limited market access, lack of sustainable assistance, and less than optimal utilization of technology. This study recommends strengthening collaboration between the government, community, and private sector, as well as optimizing digital promotion to support the sustainability of the OVOP program.